2022
DOI: 10.1186/s12879-022-07756-x
|View full text |Cite
|
Sign up to set email alerts
|

Formative acceptance of ingestible biosensors to measure adherence to TB medications

Abstract: Background Tuberculosis (TB) represents a significant public health threat in India. Adherence to antitubercular therapy (ATT) is the key to reducing the burden of this infectious disease. Suboptimal adherence to ATT and lack of demonstrated feasibility of current strategies for monitoring ATT adherence highlights the need for alternative adherence monitoring systems. Methods A quantitative survey was conducted to assess the acceptance of and will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…In a similar study, most respondents reported that they would recommend the use of similar technology in both intensive and continuation phases of TB management. 37 The majority in the same study viewed it as a useful alternative to DOT, especially among patients at risk of non-adherence. This acceptance is further enhanced by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, most respondents reported that they would recommend the use of similar technology in both intensive and continuation phases of TB management. 37 The majority in the same study viewed it as a useful alternative to DOT, especially among patients at risk of non-adherence. This acceptance is further enhanced by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The use of digital pills for the treatment of tuberculosis is being investigated by other scientists. A quantitative survey was conducted among stakeholders directly involved in tuberculosis management, revealing that digital pills are seen as an acceptable, practicable, and beneficial technology for tracking antitubercular medication adherence ( Vaz et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%